Phenomenology: Application for the exploration of the live experiences of participants and historical text - Koirala, Kamal Prasad (Pragya Darshan प्रज्ञा दर्शन, 2023)
Phenomenological research tries to describe and interpret meanings of experiences to a certain degree in-depth about the historical and sacred scripture and tried to explore the live experience of people about the phenomenon. There are mainly two types of phenomenology such as heuristic transcendental phenomenology and hermeneutic phenomenology. The heuristic transcendental phenomenology was used first by Husserl as descriptive or psychological or empirical phenomenology and it was developed as heuristic transcendental phenomenology. In heuristic transcendental phenomenology, Suspension or Reduction, Bracketing (epoche) is used to place researchers' preconceptions about the phenomenon at the edge of the writing. The hermeneutic phenomenology is used to understand the meaning of historical scripture such as Veda, Kuran, Bahagvat Geeta, Ramayan and other old scripture through the learning cycle being reflective and critical. So phenomenology works as the philosophy and qualitative research design to guide the whole research process.